Analysis of Positive Affirmation Meditation Habit on Learning Focus in elementary school - Tyas, Yohana Yesi Kusumaning; Prasetya, Andreas Erwin; Tyas, Agustina Tri Tresnaning (research, training and philanthropy institution Natural Aceh, 2025)
Meditation is one of the habits at SD Experimental Mangunan that aims to form character in children. Often, classroom learning problems are related to the focus of learning. The solution for children less focused on learning is to prepare them with meditation. This study aims to determine the effect of positive affirmation meditation on the learning focus of 1st graders at SD Experimental Mangunan. The type of research used is descriptive qualitative—data collection techniques using interviews and observation. The results of the study show that 1) positive affirmation meditation has an effect on children's learning focus, as shown by obedient children doing meditation to be calmer, and this makes children conditioned and more focused on learning, and 2) differences in obedient children in participating in meditation with those who are disobedient in participating in meditation can be seen when in class children who are obedient in meditation are more focused and not easily distracted by the situation around them, while children who are not focused during meditation tend to be more easily agitated and easily distracted by the situation around them which makes it difficult for the child to focus on studying.